2022
DOI: 10.3390/jpm12101598
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Expecting Fathers: Is Paternal Perinatal Depression a Valid Concept? A Systematic Review of Evidence

Abstract: Background. Since the identification of Couvade syndrome in the late 1950s, little attention has been dedicated to the issue of depression in expecting fathers. Objective. To quantify the extent of depression in expecting fathers and find out if they match their pregnant partners’ depression. Methods. We conducted a PubMed and ClinicalTrials.gov search using paternal depression and all its variants as terms. We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 statement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 220 publications
1
1
0
Order By: Relevance
“…Notably, with regard to the partner, there were statistically significant differences between the two groups (99.1% vs. 93.8%). This result is consistent with findings suggesting that a stable couple relationship is a protective factor from depression [ 35 , 36 ]. However, we should note that multiple support, which was preponderant in the no or minimal depressive symptoms (PHQ-9 ≤4) received all other support cases and this has determined the higher prevalence of support from relatives/friends in the more disadvantaged PHQ-9 >4 group.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, with regard to the partner, there were statistically significant differences between the two groups (99.1% vs. 93.8%). This result is consistent with findings suggesting that a stable couple relationship is a protective factor from depression [ 35 , 36 ]. However, we should note that multiple support, which was preponderant in the no or minimal depressive symptoms (PHQ-9 ≤4) received all other support cases and this has determined the higher prevalence of support from relatives/friends in the more disadvantaged PHQ-9 >4 group.…”
Section: Discussionsupporting
confidence: 93%
“…When considering mean scores across all items, the results showed that PAMA scores were higher than PAPA scores; this result is in line with most of the international literature, emphasizing that depressive symptomatology tends to occur more frequently and more severely in mothers compared with fathers during both the prenatal and the postnatal period [ 4 , 16 , 75 ]. However, there is enough evidence from the literature to legitimate paternal perinatal depression as a clinical entity, therefore deserving special attention regarding its identification and treatment [ 76 ]. When considering individual items, mothers scored higher than fathers in anxiety, depression and anger items with a small effect size, and in somatization and sleep/eating/sexual desire items with a medium effect size.…”
Section: Discussionmentioning
confidence: 99%
“…Kehamilan seorang wanita dapat mempengaruhi kesehatan psikologis dan fisik suaminya (Mazza et al, 2022). Suami mengalami tekanan psikologis pada periode kehamilan, dengan hasil penelitian melaporkan diagnosis kesehatan mental dan gejala menunjukkan bahwa sekitar 5-10% suami mengalami depresi antenatal dan 5-15% mengalami kecemasan antenatal (Darwin et al, 2017).…”
unclassified
“…Gejala depresi suami antenatal yang meningkat dikaitkan dengan kehamilan dengan prevalensi (1,9%), (4,3%) dikaitkan dengan stress yang dirasakan selama kehamilan pasangan mereka dan (2-3%) suami dikaitkan dengan kecemasan yang dirasakan dalam kehamilan (Underwood et al, 2017). Suami yang mengalami kecemasan mengatakan mengalami perasaan yang tidak menentu karena memikirkan risiko kehamilan istri (Mazza et al, 2022). Suami yang mengalami kecemasan mengatakan mengalami kesulitan tidur karena cemas, dengan presentase selalu (32%), sering (22%), kadang-kadang (30%) dan tidak pernah (16%) (Nugraha, 2020).…”
unclassified